STUDI TENTANG PENGETAHUAN, PERILAKU DAN KEBERSIHAN PENJAMAH MAKANAN DI INSTALASI GIZI BLU RSUP Prof. Dr. R.D KANDOU MANADO - Phembriah S. Kereh; Yohanis Tomastola; Annatje J.R. Masengi (POLTEKKES KEMENKES MANADO, 2013)
Food sanitation is very important, especially in public places that closely related to theservices to the people. Hospital is one of the common places that provide public healthservices one of which is the food service to support the healing process , it is necessary toplace the food processing activities are in Nutrition installation Hospital . One thing to note isthat handlers food, because the behavior of food handlers play a role in protect the health ofpeople with diseases caused by food contamination. This study aims to transform anddescribe the knowledge, attitudes, and personal hygiene of food handlers according to age,education and past Installation work in the department of Prof. Nutrition BLU Dr.RD KandouManado. This research is a descriptive study designed based cross-sectional approach. ThePopulation in this study amounted to 25 people which is then used as the total sample.Instrument in this Study using questionnaires. Data were processed and analyzeddescriptively with tables percentage. Results of this study indicate that for the knowledgehandlers food according to age, education and years of service in the department BLUNutrition Installation Prof. Dr. RD Kandou Manado for both categories of 16 %, just 64 % andless 20 %. For food handlers behavior according to age, education and pastInstallation work in the department of Nutrition BLU Prof. Dr. RD Kandou Manado tocategory 16 % good, 60 % fairly, less 24 % . For personal hygiene handlers foods accordingto age, education and years of service in the department BLU Nutrition Installation Prof. Dr.RD Kandou Manado for both categories of 60 %, 16 % less enough 24 % Conclusions ingeneral knowledge and behavior of food handlers in Nutrition installation BLU Prof Dr Dr RDKandou Manado good enough and for personal hygiene or personal hygiene of foodhandlers is fair.